Critical thinking development through English reading activities in higher education - Lim Seong Pek; Ahmad Tauchid (Early Publishing Group, 2026)
Critical thinking has become a central goal in higher education, particularly in English language learning where reading is expected to move beyond basic comprehension toward analysis, evaluation, and interpretation. Recent studies have increasingly emphasized the integration of higher-order thinking strategies, such as guided questioning and collaborative discussion, to promote deeper engagement with texts; however, much of the existing research focuses on instructional strategies or outcomes without clearly explaining how students’ thinking develops over time, leaving the connection between learning processes and measurable outcomes less fully explored. This study therefore aims to examine how English reading activities support the development of critical thinking among higher education students and to explore how students respond to the integration of critical thinking-oriented tasks. Using a mixed-method design, the study involved 23 undergraduate students in an English education program at a public university in Indonesia, with data collected through pre- and post-tests, reflective journals, classroom observations, and semi-structured interviews. Quantitative data were analyzed using paired samples t-tests, while qualitative data were examined through thematic analysis to identify patterns of engagement and cognitive development. The findings reveal consistent and balanced improvement in students’ abilities to analyze, evaluate, and interpret texts over time, with interpretation showing slightly stronger development, alongside a clear positive relationship between engagement and critical thinking performance. Students also demonstrated positive cognitive, affective, and behavioral responses, including high engagement, strong motivation, increased confidence, and a strong perception of the relevance and value of the tasks. These results imply that structured reading activities not only enhance critical thinking skills but also foster meaningful and engaging learning experiences, highlighting the importance of integrating cognitive, behavioral, and affective dimensions in instructional design to effectively support critical thinking development in higher education contexts.